CFD-Modeling of the Airfoil of the Blades of a Wind Power Plant with a Vertical Axis in the Ansys Fluent System - G. N. Uzakov; V. A. Sednin; A. B. Safarov; R. A. Mamedov; I. A. Khatamov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2024)
The article presents the results of research on modeling the DU-06-W-200 airfoil used in wind power plants with a vertical axis in the Ansys Fluent system, evaluating compatibility with experimental data and determining the optimal angle of attack. The DU-06-W-200 airfoil was simulated with angles of attack ranging from –15° to +15°, boundary conditions and input flow rate being of 15 m/s, operating temperature – of 23 °C, operating pressure – of 1·105 Pa, air flow rate – of 1.23 kg/m3 (airfoil chord length is of 1 m, dynamic viscosity of the air flow is 1.7894·10–5 kg/(m·s) and the type of turbulent models is SST k – omega (k – ω), k – epsilon (k – ε), whereas Reynolds number is 1.05·106). A two-dimensional geometry domain and a grid profile for the DU-06-W-200 airfoil have been created, with the number of nodes in the grid 37495 and the number of elements 36790. It was also found that the drag coefficients (Cd) SST k – omega (k – ω) for the turbulence model were equal to 0.1734, 0.0721, 0.0311, 0.0204, 0.0351, 0.0782, 0.1712, k – epsilon (k – ε) for the turbulence model were equal to 0.2065, 0.0789, 0.0318, 0.0212, 0.0359, 0.0787, 0.2019, lift coefficients (Cl) SST k – omega (k – ω) for the turbulence model were  –0.9169, –0.9169, –0.9239, –0.5394, 0.0842, 0.7416, 1.3134, 1.1229, k – epsilon (k – ε) for the turbulent model was –0.9278, –0.8674, –0.5336, 0.0848, 0. 0359, 0.0787, 0.2019 at angles of attack of the DU-06-W-200 airfoil equal to –15°, –10o, –5°, 0°, 5°, 10°, 15°, respectively. In assessing the compatibility of the model and the experimental results of the DU-06-W-200 airfoil, the conformity criterion χ2, root mean square error (RMSE), coefficient of determination (R2), and average bias error (ABE) were used. Based on the results of a study of the dependence of the ratio of the drag and lift coefficients on changes in the angle of attack, carried out using the SST k – omega (k – ω) and k – epsilon (k – ε) turbulence models, it has been found that the maximum value of the ratio of the drag and lift coefficients is 21 at the optimal angle attack inclination equal to 5°.